Influence of environmental factors on seed germination and seedling emergence of Eclipta (Eclipta prostrata) in a tropical environment - Chauhan, Bhagirath S.; Johnson, David E. (Cambridge University Press, 2008)
Experiments were conducted to determine the influence of various environmental factors on seed germination and seedling emergence of eclipta. Seed germination was completely inhibited in the dark, whereas in the light/dark it was 76, 93, and 87% at 25/15, 30/20, and 35/25 C alternating day/night temperatures, respectively. Germination was greater than 80% up to a temperature of 140 C, when seed were placed in an oven for 5 min followed by incubation at 30/20 C for 14 d, but declined progressively with a further increase in exposure temperature with no germination at 200 C. Seed germination was tolerant of salt stress but highly sensitive to water stress. Seed germinated (87 to 93%) over a pH range of 4 to 10. Seedling emergence was greatest (83%) for the seed placed on the soil surface but declined thereafter, and no seedlings emerged from a depth of 0.5 cm. Seedling emergence was slower and lower with the addition of 4 to 6 t ha−1of plant residue. The information gained from this study identifies some of the factors facilitating eclipta becoming a widespread weed in the humid tropics and might contribute to its control.